A Nonparametric Test of the Life-Cycle Rational Expectations Hypothesis. - Browning, M (Blackwell Publishing, 1989)
In a world of perfect certainty and perfect capital markets agents allocate expenditure in such a way that the marginal utility of discounted expenditure is the same in each period. In this paper we present a test of whether any particular series of discounted prices and quantities can be exactly reconciled with a utility function and marginal utility of discounted expenditure that do not change from period to period. We find that U.K., U.S. and Canadian postwar aggregate data all reject our condition, although it is not rejected for long sub-periods. We show that our results for the U.K. suggest particular modifications to the strong form of the rational expectations hypothesis that our conditions test. In fact these data are exactly consistent with a number of alternative hypotheses. From this we argue that time series data are ill suited to parametric testing of any of the competing hypotheses on the inter-temporal allocation of expenditure.